2019
DOI: 10.1002/aoc.5269
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, characterizations, crystal structures, DFT/TD‐DFT, luminescence behaviors and cytotoxic effect of bicompartmental Zn (II)‐dicyanamide Schiff base coordination polymers: An approach to apoptosis, autophagy and necrosis type classical cell death

Abstract: Two new Zn (II)‐dicyanamide (dca) 1‐D chain coordination polymers (CPs), [Zn (LOMe)(μ1‐dca)(μ1,5‐dca)]n (1) and [Zn (LOEt)(μ1‐dca)(μ1,5‐dca)]n (2) have been successfully synthesized from bicompartmental Schiff base ligands N,N′‐Bis(3‐methoxysalicylidenimino)‐1,3‐diaminopropane (H2LOMe), N,N′‐Bis(3‐ethoxysalicylidenimino)‐1,3‐diaminoproane (H2LOEt) respectively and structurally characterized using various spectroscopic protocols like 1H NMR, IR, Raman, UV–Vis, fluorescence as well as elemental analysis, TGA, PX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…The species with a large energy gap are harder and the smaller ones are softer. Since the E value of complex (1) is higher than that of complex (2), complex (1) is harder than complex (2) [28].…”
Section: Some Electronic Structure Descriptorsmentioning
confidence: 99%
“…The species with a large energy gap are harder and the smaller ones are softer. Since the E value of complex (1) is higher than that of complex (2), complex (1) is harder than complex (2) [28].…”
Section: Some Electronic Structure Descriptorsmentioning
confidence: 99%
“…Being a time-dependent phenomenon, the electronic transitions and consequently the electronic spectra of compounds cannot be modelled by DFT simulations, instead has to use time-dependent (TD-DFT) simulations which employs Tamm-Dancoff approximations [50,51]. We used TD-DFT simulations with CAMB3LYP functional and cc-pVDZ as a basis set using IEFPCM [52] solvation model with methanol as solvent.…”
Section: Time-dependent Density Functional Theory Study For Tucatinibmentioning
confidence: 99%
“…For the TD-DFT computation of coordination polymers, many studies use finite-fragment cropped models. 37–40 We have shown that in the case of chain-like coordination polymer 4 , the use of finite models gives questionable results, even though the geometry of optimised models resembles that in the crystal. We consider emerging problems and propose an interpretation using periodic TD-DFPT calculations.…”
Section: Introductionmentioning
confidence: 99%